Dermatology Consultation in the Geriatrics Department of a Tertiary Hospital in China: A Retrospective Study of 178 Patients - Du L; Cao Z; Han C; Wei J; Li M; Zhang C (Dove Medical Press, 2024)
Lingyun Du,1 Zhiqiang Cao,2 Changyu Han,1 Jingjing Wei,1 Mingming Li,1 Chunhong Zhang1 1Department of Dermato-venereology, the Second Hospital of Shandong University, Jinan, 250033, People's Republic of China; 2Department of Dermatology, The Second Affiliated Hospital, Xi'an Jiaotong University, Xi'an, Shaanxi, 710004, People's Republic of ChinaCorrespondence: Chunhong Zhang, Department of Dermato-venereology, the Second Hospital of Shandong University, Jinan, 250033, People's Republic of China, Tel +86-531-85875027, Fax +86-531-88962544, Email aliu133@163.comObjective: Dermatological consultation plays an important role in diagnosing and treating skin diseases in the Department of Geriatrics. The objective of this study is to provide an analysis of the factors leading geriatric inpatients to seek dermatological consultation, aiming to facilitate accurate diagnosis and effective treatment of skin diseases by healthcare professionals specializing in geriatrics and dermatology.Methods: The electronic health records of hospitalized patients in the Department of Geriatrics who applied for dermatological consultation at the Second Hospital of Shandong University from June 1, 2022, to June 1, 2023, were retrieved. Sex, age, number of consultations, reason for dermatology consultation, and final diagnosis by dermatologists were reviewed.Results: A total of 216 consultations of 178 patients (n=178, 95 men and 83 women) were collected in this study, of whom 153 (86.0%) required only one consultation, 19 (10.7%) required two consultations, and 4 (2.2%) required three consultations. The reasons for dermatology consultations were divided into three categories: the first was for the definitive diagnosis of a new skin condition that developed during the patient's hospitalization (n=165, 76.4%), the second was for the follow-up of the condition and adjustment of medication (n=40, 18.5%), and the third was for the evaluation of the patient's disease that existed before admission to the hospital (n=11, 5.1%). In 165 consultations, most of these diseases (n=131, 79.4%) can be diagnosed by patients' conscious symptoms and clinical manifestations. Some of them need to be diagnosed or differentially diagnosed with the help of supplementary examinations, such as microscopic examination of scabies or fungi, and pathological examination.Conclusion: This study summarized the reasons for dermatology consultations for geriatric inpatients and found that dermatitis/eczema and infectious diseases were the common types of diseases consulted. The findings of this study contribute to the enhanced comprehension and management of dermatological conditions in hospitalized patients by geriatricians, as well as facilitating more efficient diagnosis and treatment by dermatologists.Keywords: geriatrics, dermatology consultation, skin diseases